2010
DOI: 10.1269/jrr.90130
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Stereotactic Radiosurgery for Patients with Non-Small Cell Lung Cancer Metastatic to The Brain

Abstract: We evaluated the treatment outcome of stereotactic radiosurgery (SRS) alone, allowing for salvage with repeat SRS or fractionated radiotherapy, for managing patients with brain metastases from non-small cell lung cancer (NSCLC). From October 1998 through November 2008, 84 patients with NSCLC metastatic to the brain were treated with linac SRS. The marginal dose of SRS ranged from 12 to 20 Gy. Twenty-one patients underwent salvage radiotherapy and repeat SRS was used for 12. The 1- and 5-year overall survival r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
48
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(49 citation statements)
references
References 31 publications
1
48
0
Order By: Relevance
“…These results are consistent with previously published studies. 24,30 There were multiple statistically significant factors that influenced survival, including sex, age, primary status, prior WBRT, KPS score, marginal dose, and tumor characteristics such as histology subtype, tumor volume, and number of metastases.…”
Section: Discussion Survivalmentioning
confidence: 99%
See 1 more Smart Citation
“…These results are consistent with previously published studies. 24,30 There were multiple statistically significant factors that influenced survival, including sex, age, primary status, prior WBRT, KPS score, marginal dose, and tumor characteristics such as histology subtype, tumor volume, and number of metastases.…”
Section: Discussion Survivalmentioning
confidence: 99%
“…The local tumor control after SRS in NSCLC patients consistently exceeds 80% in the literature. 24,30 The utilization of SRS for NSCLC metastases has increased significantly and appropriately abbreviatioNs GKRS = Gamma Knife radiosurgery; KPS = Karnofsky Performance Scale; NSCLC = non-small cell lung cancer; RPA = recursive partitioning analysis; RTOG = Radiation Therapy Oncology Group; SRS = stereotactic radiosurgery; WBRT = whole-brain radiotherapy. obJect Non-small cell lung cancer (NSCLC) is the most frequent cancer that metastasizes to brain.…”
mentioning
confidence: 99%
“…Rades et al concluded that performance status, age, and extracranial metastases have a potential effect on survival 13 . Mariya et al revealed that the factors significantly affecting overall survival were primary tumor control, performance status, and number of brain metastases 14 . Nieder et al 7 found that the only factors influencing survival were primary tumor control and performance status.…”
Section: Discussionmentioning
confidence: 99%
“…Such limited metastases are referred to as oligometastases. Local therapy, such as surgery and radiotherapy, has been applied successfully in appropriately selected patients, especially for patients with either brain metastasis alone or those with adrenal metastasis alone [31][32][33][34] . Recently, Yano et al reported a retrospective study reviewing their therapeutic experience with postoperatively recurrent NSCLC patients and demonstrated that a histology of adenocarcinoma, a longer disease-free interval (≥ 1 year) and the use of local therapy are significantly preferable prognostic factors for the postrecurrence OS of patients with distant metastasis alone [6] .…”
Section: Treatment Of Oligometastatic Recurrencementioning
confidence: 99%